2021
DOI: 10.1055/a-1550-2503
|View full text |Cite
|
Sign up to set email alerts
|

Detection of soluble biomarkers of pancreatic cancer in endoscopic ultrasound-guided fine-needle aspiration samples

Abstract: Background Biomarkers are urgently needed for pancreatic ductal adenocarcinoma (PDAC). Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is the cornerstone for diagnosing PDAC. We developed a method for discovery of PDAC biomarkers using the discarded EUS-FNA liquid. Methods This retrospective study included 58 patients with suspected pancreatic lesions who underwent EUS-FNA. Protein extracts from EUS-FNA liquid were analyzed by mass spectrometry. Proteomic and clinical data were modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Sekita-Hatakeyama et al ( 26 ) performed NGS for liquid-based cytological specimens to assess the mutations of KRAS, TP53, CDKN2A, SMAD4, and PIK3CA, which could improve the diagnostic efficiency of FNA for pancreatic tumors. The PDAC protein found by Souche et al ( 27 ) in liquid-based cytological specimens could be a potential biomarker for pancreatic tumors.…”
Section: Discussionmentioning
confidence: 91%
“…Sekita-Hatakeyama et al ( 26 ) performed NGS for liquid-based cytological specimens to assess the mutations of KRAS, TP53, CDKN2A, SMAD4, and PIK3CA, which could improve the diagnostic efficiency of FNA for pancreatic tumors. The PDAC protein found by Souche et al ( 27 ) in liquid-based cytological specimens could be a potential biomarker for pancreatic tumors.…”
Section: Discussionmentioning
confidence: 91%
“…Detection of proteins in the LN FNA supernatant that were not detectable from capillary blood or serum supports the conclusion that we are sampling lymph node tissue and/or lymph-associated proteins, as opposed to blood contaminants introduced by the procedure. There has been interest, particularly in cancer, in proteomic analysis of FNA supernatants -from possible malignant tissue or metastases containing LNs -to screen for the presence of cancer cells [44][45][46]. Such studies focus on detecting cellular abundance (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown how protein extracts from EUS‐FNAC‐derived fluid can be analyzed by mass spectrometry and proteomics with an application of protein signature score for pancreatic ductal adenocarcinoma screening and diagnosis 74 . Moreover, this signature score could help identify pancreatic ductal adenocarcinoma in a vast majority of EUS‐FNAC inconclusive cases on cytology.…”
Section: Ancillary Techniques With Eus‐fna Icing On the Cakementioning
confidence: 99%